General geology and limestone cave geomorphology assessment of Subong, Gua Musang - Siti Nur Liyana Adzman (2013)
The area of study located between the latitude 101˚55'15- E to 101˚58'00 E and longitude 4˚57'30-N to 4˚55'15-N positioned in Subong, Gua Musang, Kelantan. The area mainly consist of sedimentary and metamorphic rock which belong to Gua Musang Formation. The objectives of research are to produce detailed and comprehensive geological map of the study area, to determine the geomorphology of Subong's cave and to apply passing compass method on Subong's cave. To fulfil this objectives, several methods are used such as Field Work Geological Mapping, Thin Sectioning and Passing Compass Method. The results shows that the geomorphology of Subong cave is consisting of several structure and chamber which each have their unique specific characteristic.